University students’ view of University Social Responsibility - Lugo Muñoz, Mar; Lucio-Villegas Ramos, Emilio (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
University Social Responsibility has a very relevant role in higher education because it offers an integral vision in key processes in management, teaching, research and extension. This study was carried out at the University of Cadiz with the aim of finding out the opinion of university students on USR. The methodology is non-experimental, quantitative, descriptive and a questionnaire was applied to 169 undergraduate students of Early Childhood and Primary Education. The results express a framework for improvement in the practice and implementation of the socially responsible model.